In situ enzymatic activity of transglutaminase isoforms on brain tissue sections of rodents: A new approach to monitor differences in post-translational protein modifications during neurodegeneration - Schulze-Krebs, Anja; Canneva, Fabio; Schnepf, Rebecca; Dobner, Julia; Dieterich, Walburga; von Hörsten, Stephan (Brain Research, 2016)
Mammalian transglutaminases (TGs) catalyze the irreversible post-translational modifications of proteins, the most prominent of which is the calcium-dependent formation of covalent acyl transfers between the ?-carboxamide group of glutamine and the ?-amino-group of lysine (GGEL-linkage). In the central nervous system, at least four TG isoforms are present and some of them are differentially expressed under pathological conditions in human patients. However, the precise TG-isoform-dependent enzymatic activities in the brain as well as their anatomical distribution are unknown. Specificity of the used biotinylated peptides was analyzed using an in vitro assay. Isoform-specific TG activity was evaluated in in vitro and in situ studies, using brain extracts and native brain tissue obtained from rodents. Our method allowed us to reveal in vitro and in situ TG-isoform-dependent enzymatic activity in brain extracts and tissue of rats and mice, with a specific focus on TG6. In situ activity of this isoform varied between BACHD mice in comparison to their wt controls. TG isozyme-specific activity can be detected by isoform-specific biotinylated peptides in brain tissue sections of rodents to reveal differences in the anatomical and/or subcellular distribution of TG activity. Our findings yield the basis for a broader application of this method for the screening of pathological expression and activity of TGs in a variety of animal models of human diseases, as in the case of neurodegenerative conditions such as Huntington?s, Parkinson?s and Alzheimer?s, where protein modification is involved as a key mechanism of disease progression.
EVALuna2:2088